Green/red light-sensing mechanism in the chromatic acclimation photosensor - Nagae, Takayuki; Fujita, Yuya; Tsuchida, Tatsuya; Kamo, Takanari; Seto, Ryoka; Hamada, Masako; Aoyama, Hiroshi; Sato-Tomita, Ayana; Fujisawa, Tomotsumi; Eki, Toshihiko; Miyanoiri, Yohei; Ito, Yutaka; et al. (Science advances, 2024)
Certain cyanobacteria alter their photosynthetic light absorption between green and red, a phenomenon called complementary chromatic acclimation. The acclimation is regulated by a cyanobacteriochrome-class photosensor that reversibly photoconverts between green-absorbing (Pg) and red-absorbing (Pr) states. Here, we elucidated the structural basis of the green/red photocycle. In the Pg state, the bilin chromophore adopted the extended C15- Z , anti structure within a hydrophobic pocket. Upon photoconversion to the Pr state, the bilin is isomerized to the cyclic C15- E , syn structure, forming a water channel in the pocket. The solvation/desolvation of the bilin causes changes in the protonation state and the stability of π-conjugation at the B ring, leading to a large absorption shift. These results advance our understanding of the enormous spectral diversity of the phytochrome superfamily. The structure of the cyanobacterial chromatic acclimation photosensor revealed a unique mechanism for green and red light sensing.